Effect of Fartlek k on the Increase in Vo2max - Guntur Gaos, Mochmad (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The main purpose of this research is as one of the outputs and tasks of the coaching science course, as well as to find out the effect of fartlek training on increasing VO2Max in pjkr students of the 2023 batch. VO2Max is a key indicator of cardiovascular fitness and endurance which is very important in the activities of physical education students. The method used in this study is an experiment with a one-group pretest-posttest design. The sample consisted of 40 students who were divided into experimental and control groups, each totaling 20 students. Fartlek exercises were performed for 16 sessions in one month with significantly increased intensity. VO2Max measurements are taken before and after treatment using a bleep test. The results showed that there was a significant increase in the VO2Max of students who underwent fartlek training compared to the control group who did not receive treatment. Thus, it can be concluded that fartlek exercises are effective in increasing the VO2Max of pjkr students of the class of 2023.